Clinical features and familial mutations in the coexistence of Wilson's disease and Alport syndrome: A case report - Wang, Ying; He, Qingnan; Dang, Xiqiang; Wu, Xiaochuan; Li, Xiaoyan (Frontiers in Pediatrics, 2023)
Background: Alport Syndrome (AS) and Wilson disease (WD) are genetic diseases those could lead to kidney damage. Herein, we report the clinical features and mutations in a patient with WD and X-linked AS. Case presentation: The proband was a 12-year-old boy diagnosed Alport Syndrome (AS) coexisting with Wilson disease (WD) at the age of 11 years. The patient had a medical check-up when he was 4 years and 8 months. Laboratory tests revealed elevated liver enzymes, decreased serum ceruloplasmin, increased 24-hour urinary copper excretion and one variant in the ATP7B gene. Then, the patient was diagnosed with WD. After two months of treatment with D-penicillamine and zinc salt, his liver function had recovered to normal levels but presented with microscopic hematuria. The hematuria did not solve after switching the D-penicillamine to dimercaptosuccinic acid. In addition, he presented proteinuria three years later. A renal biopsy was performed more than six years after the patient was diagnosed with WD, and electron microscopy showed the basement membrane that thickness was uneven, layered and focal torn. Copper staining was negative. Genetic analysis identified a hemizygous variant (c.1718G > A, p. Gly573Asp) in COL4A5 and a homozygous variant (c.2975C>T, p. Pro992leu) in ATP7B. He showed a urine protein-creatinine ratio less than 1.0 mg/mg after one year of follow-up, after enalapril was administered for treat AS. Conclusion: This case highlights a lack of improvement in renal manifestations after conventional treatment can be an indication for renal biopsy or genetic testing to determine the etiology in order to facilitate subsequent management. Clinicians should avoid diagnostic inaccuracies caused by diagnostic anchoring because an accurate diagnosis is essential for precise treatment and improved prognosis.